Correlation Between the Functional Connectivity of Basal Forebrain Subregions and Vigilance Dysfunction in Temporal Lobe Epilepsy With and Without Focal to Bilateral Tonic-Clonic Seizure - Fan, Binglin; Pang, Linlin; Li, Siyi; Zhou, Xia; Lv, Zongxia; Chen, Zexiang; Zheng, Jinou (Frontiers in Psychiatry, 2022)
Background and Objective: Previous research has linked subcortical brain regions to vigilance impairment in temporal lobe epilepsy (TLE). However, it is unknown whether abnormalities in the structure and function of basal forebrain (BF) subregions are associated with vigilance impairment in different TLE subtypes. We aimed to investigate changes in BF subregion structure and function in TLE patients with and without focal to bilateral tonic-clonic seizures (FBTCS) and their associated clinical features. Methods: The study included 50 TLE patients (25 without and 25 with FBTCS) and 25 healthy controls (HCs). The structural and functional alterations of BF subregions in TLE were investigated using voxel-based morphometry (VBM) and resting-state functional connectivity (RSFC). Correlation analyses were utilized to investigate links between substantially changed imaging characteristics and clinical patient data. Results: FBTCS patients had lower RSFCs between Ch_123 and the bilateral striatum and left cerebellum posterior lobe than non-FBTCS patients. FBTCS patients had lower RSFC between Ch_4 and the bilateral amygdala than non-FBTCS patients. TLE patients had lower RSFC between the basal forebrain subregions and the cerebellum, striatum, default mode network, frontal lobe, and occipital lobe than HCs. In the FBTCS group, the left Ch_123 to striatum RSFC and vigilance measures were positively correlated. In the non-FBTCS group, the left Ch_4 to striatum RSFC and alertness measure had significant negative correlations. Conclusion: These results extend our understanding of the pathophysiology of vigilance impairment in TLE and suggest that BF subregions may be critical nodes for developing and categorizing TLE biomarkers.